Preparation of Fluorine-Doped TiO2 Photocatalysts with Controlled Crystalline Structure - N. Todorova; T. Giannakopoulou; G. Romanos; T. Vaimakis; Jiaguo Yu; C. Trapalis (International Journal of Photoenergy)
Nanocrystalline F-doped TiO2 powders were prepared by sol-gel route. The thermal behavior of the powders was recorded by DTA/TG technique. The crystalline phase of the fluorinated TiO2 powders was determined by X-ray diffraction technique. It was demonstrated that F-doping using CF3COOH favors the formation of rutile along with anatase phase even at low temperature. Moreover, the rutile's phase content increases with the increase of the quantity of the fluorine precursor in the starting solution. The surface area of the powders and the pore size distribution were studied by N2 adsorption-desorption using BET and BJH methods. X-ray photoelectron spectroscopy (XPS) revealed that the fluorine is presented in the TiO2 powders mainly as metal fluoride in quantities ∼16 at %. The F-doped TiO2 showed a red-shift absorption in UV-vis region which was attributed to the increased content of rutile phase in the powders. The powders exhibited enhanced photocatalytic activity in decomposition of acetone.